APPLICATION OF THE PROBLEM BASED INSTRUCTION (PBI) LEARNING MODEL ON TUBE MATERIALS TO IMPROVE STUDENT LEARNING OUTCOMES - Sihombing, Robinson (Universitas Nias Raya, 2023)
This research aims 1) to describe tube learning by applying the Problem Based Instruction (PBI) learning model, 2) to describe improving student learning outcomes through implementing the Problem Based Instruction (PBI) learning model. This research is Classroom Action Research (PTK). The instruments used are (a) Teacher (Researcher) and Student Observation Sheets, (b) Interview Guide Sheets, (c) Documentation, (d) Field Notes, (e) Learning Results Tests. The research subjects were class IX students at SMP Swatsta Imanuel Bekasi with a total of 20 students. The research results obtained show that the Problem Based Instruction (PBI) learning model can improve student learning outcomes, especially in tube material. This is because by implementing the Problem Based Instruction (PBI) learning model students are more active in learning, understand the concept of the material better, are able to solve mathematical problems, students' analytical power towards mathematical problems increases, they are more critical in solving problems and the group learning carried out makes Students are more open in expressing their ideas. Based on the results of this research, it can be concluded that using the Problem Based Instruction (PBI) learning model can improve student learning outcomes, especially in tube material. The Problem Based Instruction (PBI) learning model should be used as an alternative in improving student learning outcomes in mathematics learning.